Malignant giant cell tumor of toe: A case report and review of literature. Issue 22 (3rd June 2022) - Hashimoto, Kazuhiko; Nishimura, Shunji; Ito, Tomohiko; Akagi, Masao; ,
Abstract: Introduction: A giant cell tumor of soft tissue (GCST) is a benign soft tissue tumor that often occurs subcutaneously in the extremities. Rare cases of malignant GCST have been reported, but its pathogenesis remains unclear. Patients concerns: We report a case of a 68-year-old man who noticed a painless mass on his second toe one and a half years ago. He visited the Department of Dermatology at our hospital. Magnetic resonance imaging revealed a soft tissue tumor, surrounding the distal aspect of the second toe. Diagnosis: A biopsy of the tumor was performed by a dermatologist, and it revealed a malignant giant cell tumor of the toe. Interventions: He was referred to our department and underwent lay amputation for wide-margin resection. Outcomes: No recurrence or metastasis was observed 5 years after treatment. Conclusion: : Malignant GCST should be treated with wide-margin resection immediately after its diagnosis.